Synthesis of potassium niobates by the microwave-assisted solvothermal method. Issue 1 (October 2015) - Duarte, T M; Honorio, L M C; Brito, A S; Souza, J K D; Longo, E; Tranquilin, R L; Souza, A G; Santos, I M G; Maia, A S
Abstract: Potassium niobates have been synthesized by different methods, but few papers use the microwave-assisted solvothermal method, with possibility of a deeper evaluation in this area. In this work, the synthesis of KNbO3, KNb3 O8 and K4 Nb6 O17 was performed by calcinations of precursors obtained by the microwave-assisted solvothermal method. This study evaluates the influence of various synthesis parameters such as reaction time, pH of the reaction medium, K+ concentration in the precursor solution. The results show the formation of different niobates, KNbO3, KNb3 O8, K4 Nb6 O17, depending on the short and long-range order of the precursor used in the post annealing process.